GE_GERICHTE P/22727/2015 vom 19. Juni 2024 - GE Cour de justice (2024)
INSTIGATION;PEINE PÉCUNIAIRE;IMPUTATION;VIOLATION DU SECRET DE FONCTION(DROIT PÉNAL);PRINCIPE DE L'ACCUSATION | CP.24; CP.34; CP.51; CP.320; CPP.9; CPP.325.al1.letf